PENGARUH TEMPERATUR DAN WAKTU REAKSI MINYAK JELANTAH DENGAN ZEOLIT ALAM PADA PRODUKSI BIOFUEL - Febriana, Ida; Ramadhini, Tri Karimah; Aulia, Tri (Politeknik Negeri Sriwijaya, 2020)
Biofuel is an alternative fuel that can be produced with organic resources such as vegetable oil and animal fat. One of the items that can be converted into biofuels is waste cooking oil. Waste cooking oil has a long hydrocarbon chain that allows it to be cracked. Biofuels are produced by catalytic cracking process. Catalytic cracking is a process in which complex hydrocarbon fractions are cracked into smaller, more valuable hydrocarbon. In this process natural zeolite is used by its ability on cracking hydrocarbon fractions. This research aims to get optimum condition of converting waste cooking oil to biofuels and to know the effects of temperature and reaction time on its products produced. The amount of raw materials, type of catalyst and amount of catalyst is preferred as controlled variable in this research, whereas temperature and reaction time is preferred as statistical variable. Biofuels are produced by various temperature such as 280°C-320°C and reaction time on 30 minutes-150 minutes using natural zeolite catalyst which accelerate the reactions. According to the process that has been done, this research obtained optimum process condition at the highest temperature 320°C which reviewed by its yield produced percentage in amount of 9.8147%. Based on various tested parameters including density, viscosity, flash point and GC-MS, biofuels has required the quality standard.